INNOVATIVE PROJECT AS OBJECT OF DESIGN MANAGEMENT - Vasily Tur (Вестник Северо-Кавказского федерального университета, 2022)
In work the author's concepts «Innovation» and «innovative project» are formulated; specific features of the innovative project are defined; stages of its realization are in detail considered; the necessary sequence of the actions of the manager preceding implementation of the innovative project is formulated.